(untitled) (Boletin Médico de Postgrado, 2020)
This essay presents a reflection of how life should be studied from a complex theoretical perspective in order to explain how the determinants influence the health/disease process in public health. The article explains the need to deepen the theoretical study of life as the center of a process that determines the relation between health/illness and death of the human being which deserves to be studied from a much broader perspective, understanding the complexity of life as a dynamic process and in constant transformation, as opposed to the traditional view that takes into account only the biological aspects of life. This view includes the importance of aspects which influence the human vital process such as lifestyle, living conditions and the socio-cultural context where the person lives.